2014
DOI: 10.1002/cphc.201300910
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatation of Zeolite H‐ZSM‐5: A Combined Microscopy and Spectroscopy Study

Abstract: A variety of phosphated zeolite H-ZSM-5 samples are investigated by using a combination of Fourier transfer infrared (FTIR) spectroscopy, single pulse (27)Al, (29)Si, (31)P, (1)H-(31)P cross polarization (CP), (27)Al-(31)P CP, and (27)Al 3Q magic angle spinning nuclear magnetic resonance (MAS NMR) spectroscopy, scanning transmission X-ray microscopy (STXM) and N2 physisorption. This approach leads to insights into the physicochemical processes that take place during phosphatation. Direct phosphatation of H-ZSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(98 citation statements)
references
References 213 publications
(181 reference statements)
6
92
0
Order By: Relevance
“…In contrast, 32 we have shown that the intensity of the bands corresponding to terminal Al-OH groups decrease significantly after the phosphatation of H-ZSM-5. 19,58 From the X-ray absorption maps in Figure 9 it follows that location of phosphorus and aluminum does not correlate, which further indicates that most phosphorus does not interact with aluminum in zeolite H-ferrierite. A schematic representation of this effect is shown in Scheme 1c.…”
Section: Ferrieritementioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, 32 we have shown that the intensity of the bands corresponding to terminal Al-OH groups decrease significantly after the phosphatation of H-ZSM-5. 19,58 From the X-ray absorption maps in Figure 9 it follows that location of phosphorus and aluminum does not correlate, which further indicates that most phosphorus does not interact with aluminum in zeolite H-ferrierite. A schematic representation of this effect is shown in Scheme 1c.…”
Section: Ferrieritementioning
confidence: 91%
“…From Figure 8 it can be observed that H-ferrierite steamed at 500 °C, shows a strong contribution of the 27 Al MAS NMR resonance at 32 ppm, corresponding to {Al} EF species. 19,68,69 The resonance at 30 ppm is even more pronounced for H-ferrierite steamed at 600 °C. Furthermore, in Figure 9, the Al K- The inaccessible nature of these {Al} EF species follows from our results as well.…”
Section: Ferrieritementioning
confidence: 92%
“…Interestingly, with an increased 288 amount of phosphorus (6PZ sample), only one peak is observed at 289 intermediate temperature (ca. 610 K), although with a pronounced 290 tail toward higher temperature, suggesting that strong "zeolitic" 291 Brønsted sites progressively disappear by P addition[42]. Together 292 extraframework Lewis acid sites also disappear, while weaker 293…”
mentioning
confidence: 94%
“…35 According to the literature, TPD can be performed by a wide 36 variety of methods: the analyses of the outlet gas stream with 37 techniques such as mass spectroscopy [11,12], thermal conductivi- 38 ty detectors (TCD) [12][13][14], flame ionization detectors (FID) [12], or 39 a combination of infrared and mass spectrometry (IRMS) detectors 40 [10,15,16]. Alternatively, the heat flow curve is acquired during 41 this process and the amount of desorbed species as a function of 42 time is measured either by mass variation, using a microbalance 43 [11,17,18], or by particular systems such as a Quantachrom 44 Autosorb-1 instrument [19], NH 3 -TPD apparatus (Nihon Bell, 45 Japan, BEL-CAT) connected to a Q-Mass analyser (Pfeiffer Vacuum, 46 Omnistar GCD301, Germany) [20]. A new sensor for the detection 47 of ammonia, based on zeolites, has been recently proposed 48 although the comparison with conventional measurements is still 49 unclear [21].…”
Section: Introductionmentioning
confidence: 99%
“…Since it was firstly reported, the phosphorus modification of ZSM-5 has been applied to different reactions such as fluid catalytic cracking, toluene alkylation, and also methanol to hydrocarbons [108]. The introduction of phosphorus also play an important role in enhancement the hydrothermal stability of the ZSM-5, as it was first reported by Lischke et al [107], and confirmed by other researchers [109][110][111][112][113]. This is especially important for the application of ZSM-5 in the MTH reaction, since water is present in the reaction media and causes progressive dealumination and therefore irreversible deactivation of the catalyst.…”
Section: 6phosphorus Modified Zsm-5mentioning
confidence: 72%